Then and Now: COVID-19 Pandemic Lockdown Misfire Atmospheric Methane over India - Manoj Hari; Rajesh Kumar Sahu; MS Shyam Sunder; Bhishma Tyagi (Aerosol and Air Quality Research)
Abstract COVID-19 lockdown resulted in the revival of the environment due to reduced emissions of various pollutants globally. In particular, aerosols, NOx and SO2 showed significant reductions at most places. However, the greenhouse gases are not necessarily following this reduction everywhere. In most areas, a decrease in NOx increases methane (CH4) concentration by enhancing the lifetime, but also results in decreased concentrations with reduced emissions. Analyzing the atmospheric CH4 variations during the COVID-19 lockdown over India is crucial as India is one of the regions with high seasonal variability of CH4. The present study has analyzed the tropospheric CH4 trends over India during the pre-monsoon season (March-May) for 2003-2021 using AIRS data. The study analyzed the lockdown variations (24 March-31 May) of tropospheric CH4 over India with the same period of 2019 and 2021 using TROPOMI to find the changes in CH4 concentrations over different regions of India due to lockdown. Our results capture the undeviating north (low)-south (high) gradient in the CH4 concentration with anticipated regional intensifications, likely, in the eastern and western coastal regions, with more comprehensive details than it ever has been presented before.